Theoretical study on a water muffler. Issue 1 (May 2016) - Du, T; Chen, Y W; Miao, T C; Wu, D Z
Abstract: Theoretical computation on a previously studied water muffler is carried out in this article. Structure of the water muffler is composed of two main parts, namely, the Kevlar- reinforced rubber tube and the inner-noise-reduction structure. Rubber wall of the rubber tube is assumed to function as rigid wall lined with sound absorption material and is described by a complex radial wave number. Comparison among the results obtained from theoretical computation, FEM (finite element method) simulation and experiment of the rubber tube and that of the water muffler has been made. The theoretical results show a good accordance in general tendency with the FEM simulated and the measured results. After that, parametric study on the diameter of the inner structure and that of the rubber tube is conducted. Results show that the diameter of the left inner structure has the most significant effect on the SPL of the water muffler due to its location and its effect on the diameter ratio D2/D1.